ENGLISH LANGUAGE TEACHING AND EFL TEACHER COMPETENCE IN INDONESIA - Urip Sulistiyo (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
This paper presents an overview of English language teaching and English as a Foreign Language (EFL) teacher education in Indonesia. Several factors appear to impede the success of teaching and learning EFL in Indonesia. Teacher qualifications and low English proficiency, classroom size, students’ motivation, classroom-oriented learning, and limited sources of learning are factors that influence EFL teaching and learning success. There are several constraints at work between language policy and language teaching classroom practices in Indonesia. First, students have very different motivations and background traits, which make it difficult to design and resource a single curriculum that suits all (or most) students across the country. Second, inadequate funds mean low wages for teachers, poor resourcing and the likelihood of large class sizes. Low teacher salaries cause the majority of teachers to work in additional jobs outside of school hours, which reduces the time they can allocate to lesson preparation, efforts to improve teaching practices and undertaking development to enhance their professional knowledge. Third, the influence of policy and curriculum politics is a constraint to language learning. In EFL teaching and learning contexts, teacher competence is essential to facilitating successful English exposure and learning during classroom activities. A number of Indonesian scholars are aware of this importance—for example, Soepriyatna (2012) identified the domains of EFL teachers’ competence in Indonesia. These domains can inform teacher education programs to design the curriculum in ways that align with the needs of EFL teachers during their classroom preparation.